Dimensions of the Meaning of Law: Milović, Miroslav: Law as potency. Essays on the philosophy of law, "Lađa" Library, Gradac, Čačak 2023. - Jakovljević, Dragan (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
The last, posthumously published book of the important middle-generation Serbian philosopher Miroslav Milović (1955-2021), a former professor at the Faculty of Law at the University of Brasilia, brings a selection of his recent essays translated from the Portuguese language, accompanied by an Introduction by Vanja Grujić.